Chip Thickness and Microhardness Prediction Models during Turning of Medium Carbon Steel - S. A. Alrabii; L. Y. Zumot (Journal of Applied Mathematics)
Cutting tests were conducted to medium carbon steel using HSS tools with cutting fluid. The experimental design used was based on response surface methodology (RSM) using a central composite design. Chips were collected at different machining conditions and thickness and microhardness measurements taken and analyzed using “DESIGN EXPERT 7” experimental design software. Mathematical models of the responses (thickness and microhardness) as functions of the conditions (speed, feed, and depth of cut) were obtained and studied. The resultant second-order models show chip thickness increases when increasing feed and speed, while increasing depth of cut resulted in a little effect on chip thickness. Chip microhardness increases with increasing depth of cut. It also increases with increasing speed and feed up to a certain level beyond which further increases cause a drop in microhardness.